Denominal verbs of cognition in Croatian: derivational patterns and cognitive processes - Raffaelli, Ida (Array, 2014)
The paper deals with verbs of cognition in Croatian, an inflected language with rich derivation, and focuses on conceptual relations that accompany their lexicalization. Croatian verbs, in terms of lexicalization, can be divided in two main categories: 1. unmotivated verbs – not derived from other words, 2. motivated – derived from other words of various parts of speech. Unmotivated verbs, predominately of Old-Slavic origin, serve as a morphological basis for further derivational processes, i.e. they are stems for derivation of motivated verbs. In terms of their semantics, verbs from both groups can extend their primary meanings to other domains and thus acquire polysemous structure. In this paper we deal with a subset of motivated verbs, namely with verbs derived from nominal stems belonging to the domain of cognition. Verbs in the domain of cognition denote highly abstract concepts, but they are lexicalized via more or less concrete domains (e.g. measure, scale or even law) through the cognitive mechanisms of metonymy and metaphor. The main objective of this paper is to show how these mechanisms operate in lexicalization of Croatian verbs of cognition and which morphological processes simultaneously take part. We focus on the domain of cognition and on verbs derived from nouns via suffixation, for two reasons: first, the domain of cognition is particularly suitable for this kind of research, since nominal stems belong to different source domains and numerous types of word-formation metonymy (as distinguished by Janda (2011)), as well as conceptual metaphors participate in mapping from source domains to the analyzed target domain. Second, verbs derived from nouns via suffixation regularly appear in the same derivational construction: [[X]nominal stem [Y]derivational suffix [Z]infinitive ending]V. Verbs with this morphological structure were extracted from CroDeriV, a large morphological database consisting of app. Croatian 14 000 verbs segmented into lexical and derivational morphemes. The database enables the detection of all combinations of particular stems and affixes and provides information on distribution of particular morphological constructions. The total number of recorded denominal verbs in CroDeriV is 1234. Out of that number there are 52 verbs belonging to the domain of cognition. This domain comprises unmotivated and motivated verbs denoting different kinds of mental processes (e.g. to think, to ponder, to imagine, to believe etc.). Detected denominal verbs of cognition were further divided into two subgroups: 1) motivated verbs that fall into the domain of cognition through the very process of derivation, mostly via word-formation metonymy (cf. Figure 1), and 2) motivated verbs whose primary meaning falls into other domains and is then extended to the domain of cognition via metaphor. This kind of analysis provides a more thorough insight into the lexical architecture since it accounts for the simultaneity of derivational and cognitive processes and stresses their equal importance in the lexicalization. We argue that word formation cannot be explained in isolation from cognitive mechanisms, primarily metonymy and metaphor. Although these cognitive processes have been investigated at the level of lexemes, they have a great impact on derivation as well, which is still an under-researched area. Since derivational processes play a significant role in the lexicalization of concepts in Croatian, cognitive processes that accompany them must be taken into account in order to capture and describe the complexity of lexicon structure. Theoretical basis for morphosemantic analysis as described here is given in Raffaelli and Kerovec (2008) and Raffaelli (2013). In this paper it is further expanded and substantiated with data from the large computational resource thus enabling more elaborate explanation of derivational patterns from the cognitive point of view. This approach could also be implemented for other Slavic and IE languages, pointing to regular and frequent patterns in lexicalization on both morphological and semantic level.